Removal of pyrene and benzo(a)pyrene micropollutant from water via adsorption by green synthesized iron oxide nanoparticles. (29th January 2018) - Hassan, Saad S M; Abdel-Shafy, Hussein I; Mansour, Mona S M
Abstract: Polycyclic aromatic hydrocarbons (PAHs) in water are classified as organic micropollutants, which are carcinogenic even in very low concentration (ppb). In this study the green synthesized iron oxide nanoparticles (IONPs) were green synthesized at room temperature by using pomegranate peel extract. The green synthesized IONPs were used for adsorbing benzo(a)pyrene and pyrene (PAHs) from water. Factors affecting the adsorption were investigated. These factors are: nanoparticles dose, pH, temperature, and initial concentration of PAHs. The overall results showed that the maximum adsorption capacities of IONPs towards pyrene and benzo(a)pyrene were 2.8 and 0.029 mg g −1, respectively. The thermodynamic study indicated an exothermic adsorption process of pyrene and benzo(a)pyrene. The kinetic and isotherm studies were carried out. The obtained data revealed that the adsorption process follows a pseudo-second order mechanism and obeys Langmuir isotherm model. In addition, the IONPs proved to be a potential candidate for the adsorption of pyrene and benzo(a)pyrene even after five cycles of use and regeneration. The investigation was extended using semi-pilot plant to remove the studied PAHs from artificially contaminated water. The results showed that the IONPs was capable to remove the pyrene and benzo (a) pyrene at the rate of 98.5 and 99%, respectively. It also can be used as disinfectant.